The Validation of the sickle scan technique used to diagnose sickle cell disease - Magain Mihatano Barihuta; Guelord Inkalaba; Jocelyn Kakumba Mankulu; Olivier Nzingula; Maguy Luvandu Mbenza; Nicole M. Misengabu; M Ndeme; Michel Diyi; Mbembe Bitengeli; Tresor Bayebila Menanzambi; Nsimba Miezi; José Lami Nzunzu; et al. (Orapuh Journal)
Introduction